Exosomes secreted by prostate cancer cells under hypoxia promote matrix metalloproteinases activity at pre-metastatic niches - Deep, Gagan (Mol Carcinog, 2020)
Approximately, 30 000 men die from prostate cancer (PCa) every year in the United States, mainly due to the metastasis. Thus, the key events associated with PCa metastasis are under rigorous investigation, with recent studies showing that preparation of pre-metastatic niches (PMN) in distant organs is an important step. However, the molecular basis for PMN preparation is still unclear. Hypoxia in primary tumors promotes aggressiveness; however, its precise role in metastasis is not clear. We recently reported that exosomes secreted by PCa cells under hypoxia promote stemness and invasiveness in naïve PCa cells; however, whether these extracellular vesicles also influence PMN remains unknown. In the present study, we isolated exosomes from human PCa PC3 cells under normoxic (21% O(2), exosomes secreted under normoxic condition [Exo(Normoxic)]) and hypoxic (1% O(2), exosomes secreted under hypoxic condition [Exo(Hypoxic)]) conditions, and characterized their effect (10 μg exosomes, intraperitoneal (IP) treatment every 48 hours for 4 weeks) on key biomarkers associated with PMN in nude mice. Whole animal fluorescence imaging showed that Exo(Hypoxic) treatment promotes matrix metalloproteinases (MMPs) activity in several putative metastatic sites. Histological studies confirmed that Exo(Hypoxic) treatment enhanced the level of MMP2, MMP9, and extracellular matrix proteins (fibronectin and collagen) as well as increased the number of CD11b+ cells at selective PMN sites. Furthermore, proteomic profiling of exosomes by liquid chromatography/mass spectrometry identified cargo proteins in Exo(Normoxic) and Exo(Hypoxic) as well as distinct canonical pathways targeted by them. These results suggest that exosomes secreted by PCa cells under hypoxia plausibly remodel distant PMN, and thus, could be a potential target to control metastatic PCa.